Pesquisa dos subtipos de toxina shiga e de marcadores de virulência acessórios em amostras de Escherichia coli produtora de toxina shiga (STEC) desprovidas do gene eae isoladas do reservatório animal - Freire, Caroline Fernandes [UNIFESP] (2017)
Shiga toxin-producing Escherichia coli (STEC) are food-borne pathogens being ruminant animals their main natural reservoir. STEC is responsible for causing severe human illnesses as hemorragic colitis and the Hemolytic Uremic Syndrome (HUS). Recent studies have pointed out the prevalence of non-O157 STEC serotypes associated with both sporadic cases and outbreaks of severe diarrhea. Moreover, it has been observed that several non-O157 STEC serotypes unable to cause attaching and effacing lesion (A/E) have been implicated as agents of serious human diseases and HUS. Although Shiga toxin hás a central role in the pathogenesis of STEC diseases, other accessory virulence factors may also participate in this process. Therefore, to know the distribution of stx subtypes and accessory virulence genes in non-O157 STEC isolates devoid of A/E from the animal reservoir could indicate a higher pathogenic potential of these isolates and, therefore, constitutes the aimof this study. Gene sequences related to Stx1 and Stx2 subtypes, autotransporter proteins (EspP, EspI, EpeA, Sab), adhesins (Saa), toxins (EhxA) andiron uptake protein (Irp2) were sought by PCR in 125 STEC strains isolated from sheep, goat, buffalo and cattle. STEC isolates most frequently harbor stx2 (52%) and stx1stx2 (38%), being subtypes stx1a (57%), stx1c (47%), stx2a (67%), and stx2d (38%) those most frequently identified. Distribution of subtypes varied according to the reservoir. stx1a prevailed in cattle and buffalo isolates, stx1c predominate in sheep and goat, stx2a in cattle, and stx2d prevailed in goat and buffalo. The saa, espP, ehxA, espI,epeA, sab andirp2 genes were identified in 97%, 58%, 55%, 42%, 30%, 13% and11% of the STEC isolates, respectively, and differences were also observed depending on the reservoir. espP and ehxA molecular characterization showed that variants C (90%) and A (100%) prevailed, respectively. A great diversity of serotypes and virulence profiles wasobserved independently of the isolate origin. However, serotypes O39:H49, O79:H14, O113:H21 and O178:H19 were more representative among cattle and buffalos, and serotype O5:H- among goat isolates. This study made important contributions related to the virulence profile of STEC isolates from the animal reservoir in our settings. In addition, showed that STEC isolates from cattle most frequently carry the stx2 subtypes related to human infections, and harbor virulence factors at higher frequencies.